Studies in Culture Contact : Interaction, Culture Change, and Archaeology - Cusick, James G. (Book collections on Project MUSE., 2015)
People have long been fascinated about times in human history when different cultures and societies first came into contact with each other, how they reacted to that contact, and why it sometimes occurred peacefully and at other times was violent or catastrophic. Studies in Culture Contact: Interaction, Culture Change, and Archaeology, edited by James G. Cusick, seeks to define the role of culture contact in human history, to identify issues in the study of culture contact in archaeology, and to provide a critical overview of the major theoretical approaches to the study of culture and contac.